(untitled) (Asian-Australasian Journal of Food Safety and Security, 2022)
Agricultural credit usually plays a crucial role in using optimal rates of production inputs especially for resource poor farmers. The present study aims to investigate the impact of diverse land tenant types on agricultural credit receipt as well as adequacy and utilization of receipt credits. A total of 60 samples were randomly selected for interview from Sadar Upazila of Mymensingh district. The study found three types of land tenants: owner-tenant, tenant-owner and pure-tenants. The result shows that the highest percentage of land was controlled by tenant-owner (56%) followed by owner-tenant (36%) and pure-tenant (8%) of the study areas. The result of the study shows that the owner-tenant and tenant-owner of the study areas have got more access to institutional sources of agricultural credit relative to pure-tenants because of their ability to offer land as security. The pure-tenants received lower amount of agricultural credit from Bangladesh Krishi Bank (BKB) relative to the owner-tenant and tenant-owner, but they can easily get credit from BKB, if they were able to show legal papers of the rented or mortgaged lands and a recommendation of the land owner. The study found that almost 50% received credit was used by the pure-tenant farmer for family expenditure and non-farm business rather farming. The result of regression analysis indicates that 1% increase of farm size would lead to an increase of the utilization of agriculture credit for farming purposes by 35% in the study areas. The result suggests that ensuring use of agriculture credit for farming purposes could boost up productivity of the pure-tenant farmers. Asian Australas. J. Food Saf. Secur. 2022, 6 (1), 18-26